Tibbiyotni raqamlashtirish orqali tibbiy ta’limda kadrlar tayyorlash kompetensiyasini takomillashtirish - Abdujabbarova Umida Mashrukovna, Mamadaliyeva Umida Polatovna, Ixrorova Surayyo Isroil qizi, Zuparov Ilhom Baxodirovich, Safarov Ulug‘bek Qarshiboy o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
This article presents the possibilities of using information and digital technologies when studying the course of information technologies in medicine in medical institutions of higher education. Digitalization of education and the use of digital technologies will make it possible to modernize and develop education, improve the quality of training of future specialists and adapt them to the labor market, bring education closer to science, and the education system will meet the requirements of the digital economy and digital technologies